Founder personality and start-up subsidies - Gary Chapman; Hanna Hottenrott (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
Start-up subsidies play an important role in supporting start-up innovation and performance. However, what characteristics help and hinder start-ups to seek start-up subsidies remains unclear. We study whether and how founder personality, as captured by the big five personality traits and entrepreneurial orientation, impacts entrepreneurs' seeking of start-up subsidies. We argue that greater founder openness, extraversion and entrepreneurial orientation enhance seeking of start-up subsidies, while greater founder agreeableness, conscientiousness, and neuroticism inhibits it. Additionally, we argue that entrepreneurial orientation plays a mediating role in the relationship between big five personality traits and start-up subsidies. Drawing on a large multi-sector sample of German start-ups, we find strong evidence for a positive role of founder entrepreneurial orientation. While we find little evidence for a direct effect of a founder's big five personality, we find evidence of an indirect effect through its influence on entrepreneurial orientation.
Keywords: G24; L26; O25; O31; 330; Start-up subsidies; start-up financing; entrepreneurship policy; entrepreneurial orientation; big five personality traits; venture capital